Pengaruh Pemberian Reward terhadap Motivasi Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam - Oktapiani, Marliza; Rahmawati, Yuâ€™la; Choli, Ifham (JOEAI (Journal of Education and Instruction), 2019)
This research aims to determine the effect of giving rewards on the student learning motivation in learning PAI at SMPIT Ar-Rudho Jakarta. The method used in this research is field research which is in the form of observation and distribution of questionnaires that will eventually be collected and used as the source for data analysis. The hypotheses were tested using Pearson product moment correlation to find a correlation between variable X (Giving Rewards) and variable Y (Learning Motivation). The findings of this research indicate that there is an effect of giving rewards on the student learning motivation. This can be seen from the correlation index value - (r observed) 0.401 â‰¥ (r table) 0.254 - which means that there is a strong enough influence of giving rewards on the student learning motivation. It can be concluded that the provision of rewards can increase student motivation. So that giving rewards can encourage students to be more active in the learning process at school. Keywords: Reward, Learning Motivation